Cover Image, Volume 117, Number 9, September 2016. Issue 9 (September 2016) - Banaganapalli, Babajan; Mohammed, Kaleemuddin; Khan, Imran Ali; Al‐Aama, Jumana Y.; Elango, Ramu; Shaik, Noor Ahmad
Abstract : Cover : The cover image, by Noor Ahmad Shaik et al., is based on the Article A Computational Protein Phenotype Prediction Approach to Analyze the Deleterious Mutations of Human MED12 Gene, DOI:10.1002/jcb.25499 .